Valorization of Textile Waste and Resin as Eco Roster Materials for Sustainable Building Construction - Fikram, Davi Muhammad; Christanto, Johanna Putri; Alfiansyah, Muhamad Ridho; Ts, Syafi Pramudito Athallah; Kurniasari, Marina; Ikhsan, Fauzan Ali (Sinektika: Jurnal Arsitektur, 2026)
The construction industry is facing increasing pressure to adopt sustainable practices due to environmental concerns and resource depletion. This study investigates the use of textile waste as a reinforcing material combined with a resin matrix to develop environmentally friendly roster blocks for building construction applications. In Indonesia, textile waste production has reached critical levels, with approximately 2.3 million tons generated annually and projected to increase to 3.9 million tons by 2030, unless interventions to promote a circular economy are implemented. This study focuses on transforming post-industrial textile waste into valuable composite materials that can serve as sustainable construction alternatives to conventional building materials. Through comprehensive material characterization and performance evaluation, this research aims to demonstrate the viability of textile waste and resin composites as viable construction materials while addressing waste management challenges and sustainable building requirements. The developed composites exhibit promising mechanical properties with potential applications in non-load-bearing structural elements and architectural features.